SEAWEED TISSUE CULTURE TECHNIQUE IN BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) SITUBONDO - Lusiana BR Ritonga (Journal of Aquaculture Development and Environment, 2022)
Kappapyhcus alvarezii seaweed or more commonly known as Eucheuma cottonii is a potential commodity to be developed because seaweed has many benefits. The problem found in the development of seaweed in Indonesia is the number of pests and diseases in seaweed, especially ice-ice. In vitro culture techniques have become an alternative to help overcome the problems that are often faced in the provision of seeds through conventional means. There are 6 stages in seaweed tissue culture, namely broodstock acclimatization, callus induction, callus/micropropagule regeneration, micropropagule regeneration, plantlet acclimatization and seed propagation in the sea. During the observation, water quality was still in the normal range, namely temperatures ranging from 25-30 0C, pH between 8.16-8.35 and salinity 34-36 ppt.